Exposure, motivation, and self-efficacy as determinants of English proficiency - Siti Masluha; Nadia Putri Widiana (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2026)
In this research, the researchers investigated the key factors that enabled college students outside the English major to enhance their speaking and writing abilities after completing an English course. The study employed a purposeful sample of 90 college students through a cross-sectional quantitative approach. The researchers utilized self-report surveys to assess English Exposure (X1), Learning Motivation (X2), and Self-Efficacy (X3). The researchers also applied a standard English language test alongside a self-assessment tool to gather data on English Language Proficiency (Y). The researchers adopted PLS-SEM, or Partial Least Squares Structural Equation Modeling, to examine the collected data. The findings revealed that all three independent variables significantly and positively influenced English Language Proficiency. Learning motivation emerged as the strongest predictor, with self-efficacy and English exposure following in that order. These results highlight the crucial role of students’ interest in English, their internal and external motivations, and their confidence in language abilities for proficiency improvement. Ultimately, the study concludes that educators must foster these psychological and practical elements to help non-English major students advance their language skills.